Where are we going with sentinel nodes mapping in ovarian cancer? - Kampan, Nirmala Chandralega; Teik, Chew Kah; Shafiee, Mohammed Nasir (Frontiers in Oncology, 2022)
Lymph node involvement is a major predictive indicator in early-stage epithelial ovarian cancer (EOC). There is presently no effective way to determine lymph node involvement other than surgical staging. As a result, traditional ovarian cancer surgery still includes pelvic and paraaortic lymphadenectomy. However, it might be linked to higher blood loss, lengthier operations, and longer hospital stays. The creation of a technique for accurately predicting nodal status without significant lymphadenectomy is thus the subject of ongoing research. Sentinel lymph nodes (SLN) mapping is a routine procedure in oncological surgery and has been proven to be effective and safe in cervical, vulvar, and uterine cancer. On the other hand, SLN mapping is not yet widely accepted and recognised in EOC. A thorough search of the literature was conducted between January 1995 to March 2022, using PubMed and Embase. This review included studies on lymphatic outflow of the ovaries and the sentinel lymph node method. A total of 13 studies involving 212 patients who underwent sentinel lymph node mapping for ovaries were included. Both open and laparoscopic approach are used. The most popular injection site is the ovarian ligaments, and a variety of agents are utilised, although the main markers were, technetium-99m radiocolloid (Tc-99m) or indocyanine green, either alone or in combination. Overall detection rate for SLN in ovaries is 84.5% (interquartile range: 27-100%). We suggest a standardised method for sentinel lymph node mapping in ovarian cancer. The detection rates, characterisation and true positive rates of the approach in investigations support further study. The use of ultra-staging is essential for lower-volume metastasis and reproducibility. To ascertain the clinical utility of sentinel node in early ovarian cancer, larger collaborative prospective clinical trials are necessary.